Proposition of Primary School Students’ Poetry - Rizka Amaliah; A. Syukur Ghazali; Muakibatul Hasanah (Pascasarjana UM, 2015)
Proposisi Puisi Karya Anak Sekolah DasarAbstract: Proposition can be utilized for reviewing schemata and language skills of children, either in the form of a sentence or the linnes of poetry. Arguments and predication (proposition’s content) in poetry by children shows logical relationship, with associative relationship and or colocative. Single proposition is dominant showed up on a poetry by children. Relation between proposition have formed coherence in poetry by children, but on some poetry by children in class IV there is still a relationship between proposition is not intact. Creativity of poetry writing demonstrated by the use of abstract proposition, which leads the charge on a figurative language poetic elements, imagery, and retorical device (appeared in small number). In addition, the lopoping sound into the uniqueness which appeared intensively. Proposition of poetry by children shows the development that looks through the use of the word concrete—abstract, colocative—associative relationship, and sintag-matic—paradigmatic relationship.Key Words: proposition, argument, predication, poetry by childrenAbstrak: Proposisi dapat dimanfaatkan untuk menelaah skemata dan keterampilan berbahasa anak, baik dalam bentuk kalimat maupun larik-larik puisi. Argumen dan predikasi (muatan proposisi) dalam puisi karya anak menunjukkan hubungan logis, dengan relasi kolokatif dan atau asosiatif. Proposisi tunggal muncul secara dominan pada puisi-puisi karya anak. Hubungan antarproposisi telah menben-tuk koherensi dalam puisi karya anak, tetapi pada beberapa puisi karya anak kelas IV masih terdapat hubungan antarproposisi yang tidak utuh. Kreativitas penulisan puisi karya anak ditunjukkan dengan penggunaan muatan proposisi abstrak yang mengarah pada unsur puitik berupa bahasa figuratif, ci-traan, dan sarana retorika (muncul dalam jumlah kecil). Selain itu, perulangan bunyi menjadi keunikan yang muncul secara intensif. Proposisi puisi karya anak menunjukkan perkembangan yang terlihat melalui penggunaan kata konkret—abstrak, relasi kolokatif—asosiatif, dan relasi sintagmatik—para-digmatik. Kata kunci: proposisi, argumen, predikasi, puisi karya anak